2002
DOI: 10.1001/jama.287.9.1123
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Functioning of Long-term Heavy Cannabis Users Seeking Treatment

Abstract: These results confirm that long-term heavy cannabis users show impairments in memory and attention that endure beyond the period of intoxication and worsen with increasing years of regular cannabis use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
491
7
22

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 702 publications
(562 citation statements)
references
References 50 publications
42
491
7
22
Order By: Relevance
“…Significant impairments on clinical neuropsychological (e.g., Stroop test, WCST) and experimental measures of executive control (e.g., Go/No-go task, Eriksen Flanker task, Simon Task) have been identified in a range of dependent drugusing groups (Hoff et al 1996;Bolla et al 1999Bolla et al , 2000Simon et al 2000;Rosselli et al 2001;Fillmore and Rush 2002;Salo et al 2002;Simon et al 2002;Solowij et al 2002;Kalechstein et al 2003b;Goldstein et al 2004;Lundqvist 2005;Li et al 2006;Verdejo-Garcia et al 2006;McHale and Hunt 2008). Neuroimaging studies have identified an association between these executive control deficits and dysfunction in prefrontal (particularly dorsolateral and inferior frontal), anterior cingulate, and orbitofrontal regions (Bolla et al 2001(Bolla et al , 2003(Bolla et al , 2004Goldstein et al 2001;Franklin et al 2002;Paulus et al 2002;Kaufman et al 2003;Hester and Garavan 2004;Gruber and Yurgelun-Todd 2005;London et al 2005;Tapert et al 2007;Paulus et al 2008).…”
Section: Executive Control Dysfunction In Addicted Drug Usersmentioning
confidence: 99%
“…Significant impairments on clinical neuropsychological (e.g., Stroop test, WCST) and experimental measures of executive control (e.g., Go/No-go task, Eriksen Flanker task, Simon Task) have been identified in a range of dependent drugusing groups (Hoff et al 1996;Bolla et al 1999Bolla et al , 2000Simon et al 2000;Rosselli et al 2001;Fillmore and Rush 2002;Salo et al 2002;Simon et al 2002;Solowij et al 2002;Kalechstein et al 2003b;Goldstein et al 2004;Lundqvist 2005;Li et al 2006;Verdejo-Garcia et al 2006;McHale and Hunt 2008). Neuroimaging studies have identified an association between these executive control deficits and dysfunction in prefrontal (particularly dorsolateral and inferior frontal), anterior cingulate, and orbitofrontal regions (Bolla et al 2001(Bolla et al , 2003(Bolla et al , 2004Goldstein et al 2001;Franklin et al 2002;Paulus et al 2002;Kaufman et al 2003;Hester and Garavan 2004;Gruber and Yurgelun-Todd 2005;London et al 2005;Tapert et al 2007;Paulus et al 2008).…”
Section: Executive Control Dysfunction In Addicted Drug Usersmentioning
confidence: 99%
“…Solowij et al, 1992;Solowij et al, 2002). Therefore, future research should concentrate on investigating the differential effects of each recreational drug on the different cognitive functions.…”
Section: Geusau Et Al's 2004 Findings) or Inhibitionmentioning
confidence: 99%
“…Cognitive impairments and respiratory diseases and cancer are the most probable risks at this point in time. Research into the long-term cognitive effects of cannabis use has shown differential effects to be associated with frequency and duration of cannabis use (Solowij 1998;Solowij et al . 2002).…”
Section: Differential Consequences Of Cannabis Use Through the Life-spanmentioning
confidence: 99%